Pengaruh Jarak Usaha dengan Hotel Terhadap Pendapatan dan Efisiensi Usaha Dagang Cinderamata di Daerah Kuta - Septia Utami, Ika; Purbadharmaja, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 10, Oktober 2016 (pp. 1011 - 1167), 2016)
The presence of the informal sector is considered as one of the economic sectors that emerged as a result of the growth situation of high employment. One of the emerging industries in this sector is trading businesses souvenirs. This study aims to determine the effect of distance efforts on revenue and efficiency traders souvenirs in the Kuta area. Data was collected through questionnaires and direct observation. Data processed by MANOVA techniques. Based on the results of the analysis showed that traders with distance away from the hotel business has a greater income than the traders who sell near the hotel. This is because traders with distance away from the hotel businesses pay more is lower than traders with a range of business near the hotel. In terms of efficiency, based on the results of studies addressing the efficiency of merchants with distance away from the hotel business has a greater efficiency than the merchant within a business close to the hotel.
Keywords: jarak usaha, pendapatan, efisiensi